MACROECONOMIC DETERMINANTS OF AUTOMOTIVE SALES VOLUME IN MALAYSIA: EVIDENCE FROM AN ARDL ANALYSIS - Zakaria, Nurfatehah Nazwa Mohd; Arifin, Nur Afizah Muhamad (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Malaysian economic growth depends on the development of the automotive industry. The automotive industry is significant for employment, as well as industrial output and domestic consumption. This research examines the effects of a few macroeconomic variables (GDP, inflation rate and unemployment rate) on the volume of auto sales in Malaysia. The volume of auto sales is analyzed using annual time series data from 1994 to 2024, applying an Autoregressive Distributed Lag (ARDL) for the analysis of both a long-run and short-run relationship between the above-mentioned macroeconomic variables and the volume of auto sales. The research concludes that there is a long run cointegration relationship between the volume of auto sales and each of the macroeconomic variables described. Specifically, the study finds that while the level of GDP is positively correlated with the volume of auto sales, the levels of unemployment and inflation are negatively correlated with the volume of auto sales. In addition to the long-run effects described above, the research has also identified that macroeconomic shocks will affect the volume of auto sales in different ways over time, based on the dynamics of macroeconomic shocks. The results of this research present valuable information for policymakers and industry stakeholders in terms of developing strategies to stabilize and promote long-term growth in the Malaysian automotive industry.